From war to peace : altered strategic landscapes in the twentieth century - Kennedy, Paul M. 1945- Hrsg (Yale Univ. Press, 2000)
The Great Powers and the new international system, 1919-1923 / Carole Fink -- International associationalism, the social and political premises of peacemaking after 1917 and 1945 / Charles S. Maier -- American grand strategy from World War to Cold War, 1940-1950 / Melvyn P. Leffler -- Reversal of fortune, Britain, France, and the making of Europe, 1945-1956 / William I. Hitchcock -- The making of a political system, the German question in international politics, 1945-1963 / Marc Trachtenberg -- The trials of multilateralism, America, Britain, and the new economic order, 1941-1947 / Randall B. Woods -- Third World nationalism and the Great Powers / Tony Smith -- The United States, the Cold War, and the Post-Cold War order / Philip Zelikow -- Europe after the Cold War / Gregory Flynn -- The international financial system and the nation-state / Diane B. Kunz -- Global issues and the new security agenda / Paul Kennedy